Labor of love the invention of dating - Weigel, Moira 1984- (Farrar, Straus and Giroux, 2016)
"It seems as though every week there's a new app available on your smartphone promising dates a plenty...just swipe right. A mate, on the other hand, is becoming harder and harder to find. The age-old quest for true love requires more effort than ever before. Let's face it: dating is work. Which, as it happens, is exactly where it began, in the 19th century...as prostitution. In Labor of Love, Moira Weigel dives into the secret history of dating while holding up a mirror to the contemporary dating landscape, revealing why we date the way we do and explaining why it feels so much like work. This isn't a guide to "getting the guy"; there are no ridiculous "rules" to follow in Labor of Love. This is a brilliant, fresh, and utterly original approach to help us understand how dating was invented and, hopefully, lead us closer to the happy ending that it promises"...